DEPENDENSI DALAM MODEL RESIKO INDIVIDUAL UNTUK ASURANSI JIWA KELOMPOK - Getut Pramesti; Sri Haryatmi Kartiko (Universitas Sebelas Maret, 2011)
ABSTRACT: The risk dependence of an insurance portfolio in a group life insurance can be described as the individual risk model. It is used in modeling the claim distribution of insurance contracts over a fixed period of time. The distribution computation is conducted with direct calculation throught n convolution of individual claim distribution. We discuss the impact of the risk dependence on the net value of the stop–loss premium. A third risk factor in the dependence risk model is also introduced.Key words : The risk dependence, group life insurance, individual risk model, claim, the net value of the stop-loss premium.